(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Many medieval scholars paid great attention to the development of religious sciences, as well as secular knowledge in various fields of science. One of the great scientists who created works of world significance, the famous al-Hakim at-Termizi, Abu Isa al-Termizi, wrote many books on internal and external knowledge. In his works, he expressed unique views on the history of Islam, its teachings, the theory of Sufism, the science of hadith, morality and various sects. In his work, the protection of the interests of society, the pursuit of human excellence, his honor, the advancement of science and education, his ideas, theoretical views have not lost their relevance today. He left us with a rich and great scientific legacy.